A comunicação da ciência como objeto de fronteira no Estudo do trabalho jornalístico na divulgação científica dos IF’s da Amazônia Legal - Silva, Maiara Sobral Silva (2024)
The thesis investigates the role of journalists in scientific dissemination in the Federal Institutes of the Legal Amazon, highlighting the challenges faced by the region due to its geography and historical context. The choice of the area is justified by the lack of studies and the distance from large centers. The study also reflects on the precariousness of journalistic work, focusing on the interface between public communication of science and press relations. The objective is to analyze the working conditions and scientific dissemination processes in these institutes, observing the horizontalization and participation of Amazonian actors. The research is applied, descriptive, documentary and qualitative in nature, focusing on the analysis of public communication of science in the Federal Institutes of the Legal Amazon. The methodology involved a bibliographic review, documentary analysis and questionnaires with journalists and communication managers. Communication policies and news from institutional portals were analyzed, categorizing the information according to principles of public communication. In addition, the research used the dialectical perspective to relate the different dimensions of the object studied, highlighting the working conditions of journalists in scientific dissemination. The discussion on the precariousness of work in the Public Administration goes beyond job instability and insecurity, also addressing the deterioration of working conditions. In the case of journalists in the Scientific Disclosure Department of the Federal Institutes, two main factors stand out: the non-institutionalization of this activity and Decree No. 10.185/2019, which eliminates vacant positions and prevents new competitions. The research reveals that communication professionals face unstable conditions and pressure to balance scientific accuracy with the accessibility of content for the public, which affects the quality of their work. There are also tensions in the relations between journalists and scientists, and the lack of specific training worsens the situation. The solution to these challenges includes greater collaboration and dialogue between the parties and the institutionalization of scientific disclosure in the Federal Institutes of the Legal Amazon.